2019
DOI: 10.1016/j.amjcard.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Blood Cholesterol Treatment Guidelines Among Physicians Managing Patients With Atherosclerotic Cardiovascular Disease

Abstract: The ACC/AHA blood cholesterol treatment guidelines recommend statin therapy for all patients after experiencing an acute cardiovascular event. Previous analyses have shown that physicians have been slow to adopt guidelines, and many patients remain untreated or undertreated with statins after a cardiovascular event. However, reasons for this remain unknown. This analysis used electronic medical records and patient chart data from Reliant Medical Group (Worcester, Massachusetts) to evaluate physician adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
4
14
0
Order By: Relevance
“…Furthermore, despite frequent application of lipid guidelines by cardiologists, diabetologists, endocrinologists, and clinical biochemists, there was an apparent discrepancy in the total familiarity score calculated among these specialties. These findings are comparable to a study conducted in the USA which also found a gap between knowledge and practice, and emphasized the importance of education [16]. Instances such as these may benefit from continuing medical education through lectures, workshops, and conferences, which can lead to better health outcomes [17].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, despite frequent application of lipid guidelines by cardiologists, diabetologists, endocrinologists, and clinical biochemists, there was an apparent discrepancy in the total familiarity score calculated among these specialties. These findings are comparable to a study conducted in the USA which also found a gap between knowledge and practice, and emphasized the importance of education [16]. Instances such as these may benefit from continuing medical education through lectures, workshops, and conferences, which can lead to better health outcomes [17].…”
Section: Discussionsupporting
confidence: 76%
“…It is noteworthy that using a combination of lipid guidelines can in fact lead to misinterpretation and ineffective or inadequate treatment as a result of both knowledge and behavior barriers. Once again, these issues can be addressed with reeducation, e.g., academic sessions [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…However, observational studies indicate that patients infrequently achieve these guideline‐recommended LDL‐C goals in daily clinical practice, 17‐21 with a recent analysis of US adults with health insurance in the MarketScan ® database reporting that 67% of patients with VHR ASCVD had LDL‐C ≥ 70 mg/dL (≥ 1.8 mmol/L) 21 . Multiple factors are thought to underpin this unmet treatment need, with suboptimal dosing, high rates of treatment discontinuation, and low rates of lipid‐lowering therapy (LLT) adherence commonly observed 22‐27 …”
Section: Introductionmentioning
confidence: 99%
“…Within the context of personalized medicine, these data suggest that it is reasonable to target evolocumab therapy to higher‐risk patients following a recent MI 12,29 . However, there are limited data on LDL‐C lowering with evolocumab in real‐world healthcare settings, where patient‐, physician‐, and payer‐related treatment hurdles are common 17,22‐27,30‐33 . Historically, these hurdles have included treatment discontinuation, educational needs for providers, prior authorization requirements, costs, and formulary restrictions 30‐33 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation